2014
DOI: 10.2139/ssrn.2389937
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Value Trajectories and Trader Characteristics in an Asset Market Experiment

Abstract: We report results from an asset market experiment, in which we investigate how the time path of the fundamental value trajectory affects the level of adherence to fundamentals. In contrast to previous experiments with long-lived assets, there is a phase in which fundamental values are constant before the onset of a trend. The trend is either increasing or decreasing, depending on the treatment. We compare the level of mispricing between the decreasing and increasing fundamental value trajectories. Before the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Brañas-Garza et al (2012 reported that subjects with higher CRT scores on average, chose numbers closer to the Nash equilibrium in beauty contest games. Corgnet et al (2013) and Breaban and Noussair (2014) reported that subjects with higher CRT scores tended to realise higher profit margins than those with low CRT scores in experimental asset markets. Here we are interested in the correlation between the CRT score (CRTS) and the magnitude of the initial forecast deviation.…”
mentioning
confidence: 99%
“…Brañas-Garza et al (2012 reported that subjects with higher CRT scores on average, chose numbers closer to the Nash equilibrium in beauty contest games. Corgnet et al (2013) and Breaban and Noussair (2014) reported that subjects with higher CRT scores tended to realise higher profit margins than those with low CRT scores in experimental asset markets. Here we are interested in the correlation between the CRT score (CRTS) and the magnitude of the initial forecast deviation.…”
mentioning
confidence: 99%
“…In standard finance theory, the amount of liquidity should not affect prices, as it does not change the security's fundamentals. However, ample experimental evidence suggests that liquidity significantly affects security prices: prices can be higher when liquidity is higher either through initial cash endowments or conditions which influence the C/A-ratio (Ackert et al 2006, Breaban and Noussair 2014, Caginalp et al 1998, Caginalp et al 2001, Caginalp and Ilieva 2008, Deck et al 2012, Haruvy and Noussair 2006, King et al 1993, Kirchler et al 2012, Noussair et al 2012, Porter and Smith 1995. We explore whether the amount of liquidity, measured by the C/A ratio, influences the price levels and price deviations from fundamentals in our markets.…”
Section: Hypothesesmentioning
confidence: 97%
“…By varying either coupon payments, the face value of the bond or the default probability function, different paths of (equilibrium) fundamental values can be achieved. This flexibility is important as the slope of an asset's fundamental value over time plays an important role in the experimental asset market literature (see Noussair et al, 2001, Kirchler, 2009, Noussair and Powell, 2010, Breaban and Noussair, 2014, Giusti et al, 2014, and Stöckl et al, 2014. 9…”
Section: Default Probability and Equilibrium Fundamental Valuementioning
confidence: 99%